Advancing AI initiatives in nursing academics: Case studies and insights from thought leaders - Sockolow, Paulina; Michalowski, Martin; Peltonen, Laura-Maria; Pruinelli, Lisiane; Topaz, Maxim (United States, 2026)
Artificial Intelligence (AI) is transforming the landscape of health care and nursing research and education. As key stakeholders in this transformation, nursing faculty are crucial in driving strategic and operational AI initiatives to develop appropriate competence within the workforce to ensure the safe application of these technologies in nursing and care. To discuss the ways nursing faculty can be actively involved in AI initiatives, a panel was convened at the Third International Workshop on Artificial Intelligence in Nursing (AINurse24). The panel delved into faculty involvement in AI initiatives, including research collaborations, curriculum development, ethical considerations, and institutional policymaking. Panelists describe initiatives in their school/college. The summary presents five common themes, as informed by the workshop discussions: (a) nurses will benefit from initiating AI implementation in their school/college, (b) resource commitment to AI initiatives, (c) education to support AI competencies and workforce upskilling, (d) research, and (e) ethics.